Usborne Young Reading : The Adventures of King Arthur - Angela Wilkes (London, United Kingdom Usborne Publishing Ltd., 2003)
Usbornes Young Reading books combine good stories with easy reading text for reades who have just started reading alone.
Keywords: Anthology-Traditional Literature -- Fairy Tales